Synchronous Gestures for Multiple Persons and Computers - Hinckley, Ken (UIST '03 Proceedings of the 16th annual ACM symposium on User interface software and technology, 2003)
This research explores distributed sensing techniques for mobile devices using synchronous gestures. These are patterns of activity, contributed by multiple users (or one user with multiple devices), which take on a new meaning when they occur together in time, or in a specific sequence in time. To explore this new area of inquiry, this work uses tablet computers augmented with touch sensors and two axis linear accelerometers (tilt sensors). The devices are connected via an 802.11 wireless network and synchronize their time-stamped sensor data. This paper describes a few practical examples of interaction techniques using synchronous gestures such as dynamically tiling together displays by physically bumping them together, discusses implementation issues, and speculates on further possibilities for synchronous gestures.